First insights into an exceptionally deep blue hole in the Western Caribbean: The Taam ja’ Blue Hole - Alcérreca-Huerta, Juan C.; Álvarez-Legorreta, Teresa; Carrillo, Laura; Flórez-Franco, Laura M.; Reyes-Mendoza, Oscar F.; Sánchez-Sánchez, Joan A. (Frontiers in Marine Science, 2023)
Coastal karst formations may remain unexplored by the global marine scientific research community. Knowledge provided by fishermen coupled with scientific research on karstic formations prompted us to explore the geomorphometric and physicochemical features of a submerged blue hole in the large tropical estuary of Chetumal Bay in the southeastern coast of the Yucatán Peninsula, Mexico. Differently from the well-known literature on cenotes in the Yucatán Peninsula, no references are made to blue holes in the region. Sampling and surveying of the blue hole were conducted in September 2021 by scuba, echosounders, CTD profilers, and the collection of water samples. This study revealed a previously unknown maximum water depth for the Taam ja’ Blue Hole, as it is now named, of 274.4 meters below sea level (mbsl), making it the second deepest known blue hole in the world. The Taam ja’ Blue Hole has a nearly circular shape at its surface, encompassing an area of 13,690 m2. The sides of the blue hole are steep, with slopes >80° that form a large conic structure covered by biofilms, sediments, limestone, and gypsum ledges. The blue hole mouth locates at 4.5-5.0 mbsl, at which water properties change significantly with temperature and salinity gradients of 4.9°C/m and 9.8 PSU/m, respectively. Hydrographic profiles show a stratified water column inside the blue hole consisting of a hypoxic layer (5-20 mbsl), a chemocline (50-80 mbsl), and an anoxic layer (>110 mbsl). Evaluation of anions and cations indicated that the water inside corresponds mainly to that of diluted seawater.